THE ROLE OF PUBLIC PARTICIPATION IN STRENGTHENING DEMOCRACY AND PROTECTING HUMAN RIGHTS IN INDONESIA - Napitupulu, Bong Bong Prakoso (Polteknik Imigrasi, 2024)
Abstract. Democracy in Indonesia provides space for the people to participate in the political process, with human rights (HR) serving as a fundamental element underpinning the system. Public participation plays a crucial role in strengthening democracy and protecting human rights, ensuring that government policies align with the people's interests and preventing the misuse of power. This study aims to analyze the role of public participation in enhancing democracy and improving human rights protection in Indonesia. The method used is a literature review, examining various secondary sources such as academic journals, books, research reports, and government documents related to the topic. The findings indicate that active public participation in politics, including electoral processes, policy oversight, and involvement in public policymaking, significantly contributes to strengthening Indonesia's democratic system. Additionally, public participation has proven to support human rights protection by pressuring the government to be more responsive to the people's aspirations, particularly regarding law enforcement and social justice. In conclusion, increasing public participation is essential to reinforce democracy and human rights protection. The implications are that the government needs to expand access and opportunities for political participation for all societal groups, especially marginalized ones. Recommendations include enhancing political education and providing transparent access to information so that the public can participate more actively and effectively.